Sosialisasi Perancangan Modul Ajar Matematika Materi Bentuk Bangun Kelas 1 Berbasis CRT - Rofiana Prilia Anisa; Diah Ayu Sekar Ningrum; Defita Berliani Putri; Putri Zudhah Ferryka (CV. ITTC INDONESIA, 2024)
The formation of students' character and self-confidence based on noble cultural values ​​can be formed through education and the culture around them. Culture-based learning does not just transfer or embody culture, but also utilizes culture to develop students' creativity in achieving learning goals. Learning that utilizes culture can also be called learning with the Culturally Responsive Teaching model or can be called CRT. This learning model can be used as community service with the target participants being 29 PGSD study program students. In this service there are 4 flow stages of activities, namely: Design, Preparation, Socialization and program sustainability.